Efeito da fertilização e da disponibilidade hídrica na produtividade florestal e na eficiência do uso da luz de povoamentos clonais de eucalyptus spp. em Bocaiúva,MG - Arrevillaga Lleras, Marìa Cecilia [UNESP] (2015)
The availability of water and nutrients are the abiotic factors that have most influence on the growth of plantations in the tropics. The BEPP project established in 2001 an experimental network installed in eight locations in Brazil, aimed to determining the potential growth rates in eucalyptus plantations when the nutritional and water limitations are removed. The forest department of the company Vallourec joined the project in 2005, establishing in the region of Bocaiúva (MG) two experiments, including four clones of commercial interest. The first experiment was established following a 2x2 factorial design, evaluating two levels of water availability (control and irrigated) and fertilization (traditional and extra). The second experiment evaluated the influence of water availability incorporating one more treatment: reduction of rainwater, while kept the traditional doses of fertilizer of the company. Climatic data were obtained from the meteorological station Carbonita (INMET) located in the region. In order to achieve the objectives of this study, biomass equations were developed based on cubing. Through remote sensing techniques, we analyzed and processed de satellite images from LANDSAT 5 TM + and LANDSAT 7 ETM +; estimating the Normalized Difference Vegetation Index (NDVI) and the Leaf Area Index (LAI) for each month, during 2007 and 2008. Irrigation treatments showed increases of 62% dry matter when compared to the control treatment. Extra doses of fertilization did not influence growth, indicating that the nutritional demands were satisfied with the traditional fertilization rate of the company. Experiment 1 did not registered significant differences in LAI between treatments. In Experiment 2, a decrease of 16% of the LAI showed in the irrigated plots, generated 23% of losses in timber growing. The light use efficiency (LUE) varied between 0.72 and 0.73 g MJ-1 in the treatments without ...